Optimum Portfolio Construction Using Single Index Model: An Empirical Study of Nepal Stock Exchange - Khadka, Bal Krishna; Rajopadhyaya, Umesh (The International Research Journal of Management Science, 2023)
Purpose: The purpose of this paper is to construct the optimum portfolio of eight sectors listed in NEPSE applying the Sharpe’s single index model. Design/Methodology/Approach: Adopting the judgement sampling method, eight sectors were selected for the study. The study period was taken from august 2018 to august 2021 for the three years period as this time frame is the recent bull period. During this period the market index increased from around 1100 to an all-time high index 3200. To construct the optimum portfolio, daily returns of the market and sectors were used. Cut off rate (C*) was calculated in order to form the optimum portfolio using daily basis data. Those sectors whose excess return to beta ratio is higher than cut off rate were included in the optimum portfolio. Findings: The study revealed five sectors- non-life insurance, hydro power, finance, microfinance, and development bank-form the optimum portfolio. In terms of ratio of investment in the optimum portfolio, the proportion of investment is found higher in the finance sector (36.6%) and lower in the development bank sector (11%). Furthermore, in terms of unsystematic risk, non-life insurance (3.681) and hydro power sector (3.508) are found as risky sectors compared to other sectors. This study exclusively used the bull period data to form the optimum portfolio applying the Sharpe’s single index model in a daily basis data. Implications: The finding can help the investors to make informed decisions aligned with their risk tolerance, return expectation and overall investment objectives.